From a syndrome to a social condition: providing palliative care to people with advanced dementia - Abreu, Wilson Correia de (Rev Rene, 2017)
Dementia is one of the biggest public health challenges in societies; over 35 million people worldwide live with the condition. This number is expected to triple by 2050. Substantial increases in health and social care costs are required to deal with this major public health problem. Thus, this explain why dementia has become a globally alarming issue. Dementia is a syndrome of diverse aetiology, characterised by progressive cognitive decline, functional impairment and dependence in self-care. Usually, the syndrome is associated with older people, and it is often accompanied by co-morbidities, pain and different organ dysfunctions. Studies show the bewilderment, distress and exhaustion relatives and loved ones feel when caring of people with dementia.